First record of Ascosphaera apis isolated from commercial pollen from northern Argentinian provinces - Tejerina, Marcos Raul (2021)
In recent years, the advance of deforestation and the replacement of areas intended for intensive cultivation have caused pathogens and parasites of Apis mellifera bees to emerge in regions where they had not previously been reported. Such is the case of the advancement of Ascosphaera apis, a fungus that can affect the colonies reducing the population of bee larvae and cause great economic losses to the beekeeping activity, when the disease is severe. In the north of Argentina, few studies have focused on this important entomopathogen. This is the first study of A. apis isolated from commercial pollen from Entre Ríos, Jujuy, and Misiones provinces, where its prevalence in bee colonies has not been reported to date. We identified this entomopathogen using macroscopic, microscopic, and molecular analyses, focusing on its botanical origin as a possible route of transmission of the disease. We found the pathogenicity of each strain in A. mellifera bees to be lower than 30%. The results of this study contribute to promoting the sanitary measures that may reduce the progression of this disease in local apiaries.